Humidity effect on organic semiconductor NiPc films deposited at different gravity conditions. (August 2016) - Fatima, N.; Ahmed, M. M.; Karimov, Kh. S.; Ahmedov, Kh.
Abstract: In this study, thin films of Nickel Phthalocyanine (NiPc) were deposited by centrifugation at high gravity (70g), and also at normal gravity (1g) conditions to fabricate humidity sensors. Ceramic alumina sheet, coated with silver electrodes, having interelectrode distance of 0.2l mm were used to assess the electrical properties of the sensors. Room temperature capacitance and impedance variations were measured as a function of relative humidity ranging from 25% ∼⃒ 95% at 1 kHz frequency. It was observed that sensors fabricated at 70g were more sensitive compared to sensors fabricated at 1g. Sensors fabricated at 70g exhibited 1.8 times decrease in their impedance and1.5 times increase in their capacitance at peak ambient humidity. SEM images showed more roughness for the films deposited at 70g compared to films deposited at 1g. It was assumed that surface irregularities might have increased active surface area of 70g sensors hence changed the electrical response. Impedance-humidity and capacitance-humidity relationships were modeled and a good agreement was observed between experimental and modeled data. Experimental data showed that NiPc films could be useful for instrumentation industry to fabricate organic humidity sensors.